Customer Patronage Intentions and Moderating Effect of Customer Mood on Retailscape Elements and Customer Joy: A Study of Grocery Retail Stores in Riyadh - Almotairi, Mohammed (International Review of Management and Marketing, 2021)
This research aimed to explore the retailscape components and identify the mediation impact of customer mood between retailscape elements and customer joy evidence from Retail Stores in Riyadh. The researcher identifies the research variables based on a critical review of previous literature. The research sample consists of 289 respondents from the population which includes customers of grocery retail stores in Riyadh. SEM by using smart PLS wad conducted as an analysis tool. The research concludes that retailscape elements can influence customer joy and customer patronage. As well as, the results indicate that mood of customer mediate the relationship between customer joy and retailscape. Finally, the researcher recommended that more future research may conduct and address more factors such as behavioral intentions and customer satisfaction. Keywords: Retailscape, customer joy, customer mood, Retail, customer patronage JEL Classifications: M40; M41 DOI: https://doi.org/10.32479/irmm.11184